2022
DOI: 10.1007/s40843-022-2246-2
|View full text |Cite
|
Sign up to set email alerts
|

Precursor solution chemistry via water additive enabling CZTSSe solar cells with over 12% efficiency

Abstract: High-quality absorber films are imperative for highly efficient Cu 2 ZnSn(S,Se) 4 (CZTSSe) thin-film solar cells. Precursor solution chemistry, interconnected with thin-film nucleation and the crystal growth process, should be studied insightfully. Thus, creative rationales and strategies could be proposed to improve the absorber quality, carrier characteristics, and hence device performance. However, the research on precursor solution chemistry in CZTSSe solar cells is still in its infancy. In this study, a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…Therefore, electric parameters including R S , G Sh , R Sh , A, and J 0 of solar cells are calculated to perform a comprehensive and deep understanding concerning the improvement mechanism of V OC and FF for C-110 and C-150, as summarized in Table 4. [57] By analyzing the data in Table 3 and Table 4, the increased V OC in C-110 and C-150 is mainly benefited from the higher R Sh and lower J 0 . To be specific, the higher R Sh is mainly attributed to the enhanced absorber crystalline quality revealed in Figure 2a-c and also observed from the cross-sectional SEM images of the whole device, as shown in Figure 3f-h.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, electric parameters including R S , G Sh , R Sh , A, and J 0 of solar cells are calculated to perform a comprehensive and deep understanding concerning the improvement mechanism of V OC and FF for C-110 and C-150, as summarized in Table 4. [57] By analyzing the data in Table 3 and Table 4, the increased V OC in C-110 and C-150 is mainly benefited from the higher R Sh and lower J 0 . To be specific, the higher R Sh is mainly attributed to the enhanced absorber crystalline quality revealed in Figure 2a-c and also observed from the cross-sectional SEM images of the whole device, as shown in Figure 3f-h.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, electric parameters including R S , G Sh , R Sh , A, and J 0 of solar cells are calculated to perform a comprehensive and deep understanding concerning the improvement mechanism of V OC and FF for C‐110 and C‐150, as summarized in Table 4 . [ 57 ]…”
Section: Resultsmentioning
confidence: 99%
“…CZTSSe absorber layers with additives exhibited improved crystalline quality and enhanced carrier dynamics in the devices, and achieved a device efficiency of 12.07%. 108 The band tailing and non-radiative recombination losses caused by deep-level defect states and defect clusters in the bulk of CZTSSe can be alleviated through cation doping. X. Zhao et al investigated the impact mechanism of Ga cation doping on CZTSSe material by comparing the effects of physical and chemical doping methods.…”
Section: Dmsomentioning
confidence: 99%
“…34 In addition, Zhao et al reported a simple and environmentally friendly additive strategy by adding water additives, which can improve the homogeneity and thermogravimetric characteristics of the precursor solution by adjusting the particle size and coordination behavior of the precursor solution, achieving a certified CZTSSe device with a PCE of 12.07%. 140 In 2022, an efficiency of 12.87% was achieved using a two-step cooling strategy, which can suppress the Cu Zn and Sn Zn defects and defect clusters synergistically. 141 Unlike amine-thiol, DMSO and other solvents, the fabrication of CZTSSe solars by EGME solvent is not only insensitive to oxygen and water in the air but also does not show decomposition or uneven morphology.…”
Section: Extrinsic Doping Of Egme-based Routesmentioning
confidence: 99%